2009
DOI: 10.1016/j.freeradbiomed.2009.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated-biphenyl-induced oxidative stress and cytotoxicity can be mitigated by antioxidants after exposure

Abstract: PCBs and PCB metabolites have been suggested to cause cytotoxicity by inducing oxidative stress but the effectiveness of antioxidant intervention following exposure is not established. Exponentially growing MCF-10A human breast and RWPE-1 human prostate epithelial cells continuously exposed for 5 days to 3 μM PCBs [Aroclor 1254, PCB153, and the 2-(4-chlorophenyl)-1,4-benzoquinone metabolite of PCB3 (4ClBQ)] were found to exhibit growth inhibition and clonogenic cell killing, with 4ClBQ having the most pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 39 publications
4
78
0
3
Order By: Relevance
“…As such, pre-treatment with antioxidants is anticipated to suppress ROS-mediated activation of AhR-signaling in 4-ClBQ treated cells. Pre-treatment with antioxidants (NAC; superoxide dismutase and catalase) has been shown to suppress 4-ClBQ induced increase in ROS levels and toxicity in HaCaT, and human mammary and prostate epithelial cells (Venkatesha et al, 2008; Xiao et al, 2013; Zhu et al, 2009). Pre-treatment with NAC significantly suppressed 4-ClBQ-induced increase in CYP1A1 mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As such, pre-treatment with antioxidants is anticipated to suppress ROS-mediated activation of AhR-signaling in 4-ClBQ treated cells. Pre-treatment with antioxidants (NAC; superoxide dismutase and catalase) has been shown to suppress 4-ClBQ induced increase in ROS levels and toxicity in HaCaT, and human mammary and prostate epithelial cells (Venkatesha et al, 2008; Xiao et al, 2013; Zhu et al, 2009). Pre-treatment with NAC significantly suppressed 4-ClBQ-induced increase in CYP1A1 mRNA expression (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MFI data was then normalized to control for each group at each respective time point, as indicated. 5, 14 …”
Section: Methodsmentioning
confidence: 99%
“…Regarding endometrial cancer, molecular epidemiological studies have shown how the activity of superoxide dismutase (SOD) would be lower in the endometrial cancer tissue than in the normal endometrium [43,44] and PCBs have been recently showed to activate the enzymatic activity of SOD 1 in endometrial cancer cells [45] as shown in a previous study where PCBs enhanced the activity of SOD both in MCF-10A human breast cells and RWPE-1 human prostate epithelial cells [46]. …”
Section: Polychlorinated Biphenyls and Endometrial Cancermentioning
confidence: 99%